Optical Fiber Communication Conference (OFC) 2020 2020
DOI: 10.1364/ofc.2020.w2a.47
|View full text |Cite
|
Sign up to set email alerts
|

DSP-based Mode-dependent Loss and Gain Estimation in Coupled SDM Transmission

Abstract: The capacity in space division multiplexing (SDM) systems with coupled channels is fundamentally limited by mode-dependent loss (MDL) and mode-dependent gain (MDG) generated in components and amplifiers. In these systems, MDL/MDG must be accurately estimated for performance analysis and troubleshooting. Most recent demonstrations of SDM with coupled channels perform MDL/MDG estimation by digital signal processing (DSP) techniques based on the coefficients of multiple-input multiple-output (MIMO) adaptive equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…iLMS and σ mdg . The LMS-based correction factor methods applies the correction factor proposed and validated in [12], [14], [15] to the DSP-estimated eigenvalues before estimating σ mdg . The ANN estimator uses the same structure and training data as in the long-haul case study in Section V. The results are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…iLMS and σ mdg . The LMS-based correction factor methods applies the correction factor proposed and validated in [12], [14], [15] to the DSP-estimated eigenvalues before estimating σ mdg . The ANN estimator uses the same structure and training data as in the long-haul case study in Section V. The results are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(2) and (3) indicate that the accuracy of the conventional method that estimates σ mdg based on the DSP-estimated eigenvalues, λ 2 i,MMSE , is clearly affected by the optical SNR [12]. In coupled SDM transmission, the MMSE equalizer is usually implemented by means of semi-supervised or supervised adaptive schemes, such as the well-known least mean square (LMS) algorithm.…”
Section: A Mdg Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…At a component level, MDL can be characterized by means of an optical vector network analyzer (OVNA) [4], [5] or digital holography techniques [6], [7] , while at a system level, the MDL is usually estimated from the channel transfer function obtained by the multiple-input multiple-output (MIMO) equalizer. In [8], we showed that the MDL estimation based on minimum mean square error (MMSE) MIMO equalizers depends on the signalto-noise ratio (SNR), resulting in an underestimation of the MDL at low SNR. We also proposed a correction factor that improves the estimation process for moderate levels of MDL.…”
Section: Introductionmentioning
confidence: 99%
“…The correction factor that improves the MDL estimation was initially proposed in [8] and experimentally validated in [10] for a back-to-back and single span transmission scheme using an MDL emulator at the transmitter side. In this work, we extend the experimental validation and show that the correction factor reduces the MDL estimation error both for the case of MDL emulation at the transmitter side, as well as for the in-span MDL emulation scenario.…”
Section: Introductionmentioning
confidence: 99%